RESPON PERKECAMBAHAN BENIH SORGUM Sorghum bicolor (L.) Moench TERHADAP PERLAKUAN OSMOCONDITIONING DALAM MENGATASI CEKAMAN SALINITAS - Rini, Dwi Setyo; Mustikoweni, Mustikoweni; T, Surtiningsih (Research Center for Biology-Indonesian Institute of Sciences, 2005)
The research was undertaken in two experiments. The first experiment was carried out to find out the germination capacity and vigor of sorghum seeds that consisted of four varieties namely Rio, Mandau, Sangkur and Keris. The second experiment was to determine the response of two sorghum varieties which had good germination capacities and so vigorous from the first experiment by osmoconditioning treatments. The growth media is saline soil with NaCl content 8.61% and pH 8.2. The osmoconditioning treatments were soaking seeds in each Na,SO4 0.2 M, NH4C1 0.2 M, KNO3 0.2 M solution for 48 hours and untreated sorghum seeds served as the control. The results showed that there was no interaction between varieties of sorghum seeds and osmoconditioning treatments on germination percentage but osmoconditioning treatments with Na,SO4 0.2 M and NH4C1 0.2 M could promote germination percentage of sorghum seeds on saline condition.